"You don't have to travel the world": accumulating experiences on the path toward globally competent teaching. Issue 3 (2nd July 2016) - Parkhouse, Hillary; Tichnor-Wagner, Ariel; Cain, Jessie Montana; Glazier, Jocelyn
Abstract : As classrooms become increasingly diverse and students need more complex skills for collaboratively addressing transnational issues, we need a better understanding of the factors that contribute to globally competent teaching. Education research has highlighted the benefits of study abroad and overseas teaching, as well as local cross-cultural immersion, but these options are not always feasible. We sought to identify the various means by which teachers develop global competence. Through this qualitative case study of 10 global educators, we found that international travel, though present in some instances, was not always necessary. In fact, it was an accumulation of experiences that prompted teachers to incorporate global perspectives, lessons, and skill development throughout their careers. Thus, globally competent teaching may be better conceptualized as a path, rather than as an end goal.